Determinants of Learning Achievement in Islamic Education: The Roles of Students’ Perceptions, Attitudes, and Classroom Management - Enung Nugraha; E. Syarifuddin; Syaza Hazwani Zaini; Badrudin Badrudin; Aan Ansori (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Globally, learning achievement in higher education is increasingly understood as the product of both academic and non-academic factors, especially within faith-based institutions where pedagogical practices intersect with religious values. This study examines how students’ perceptions of assessment systems, istiqomah (consistency) attitudes, and classroom management shape learning achievement in Islamic higher education contexts. The research aims to identify which factors most strongly predict academic performance and how Islamic character formation interacts with instructional processes. Using a quantitative survey design, data were collected from 190 students enrolled in the Evaluation of Learning course at UIN Sultan Maulana Hasanuddin Banten, Indonesia, and Universiti Pendidikan Sultan Idris, Malaysia. Partial Least Squares (PLS) analysis was applied to test the structural model. The results show that students’ positive perceptions of fair and transparent assessment practices and effective classroom management significantly enhance learning achievement. However, istiqomah attitudes do not directly influence academic outcomes, indicating that spiritual consistency requires pedagogical mediation to translate into academic engagement. The study concludes that improving learning quality in Islamic higher education depends on integrating equitable assessment and supportive classroom climates. Implications include strengthening instructional management and aligning assessment practices with Islamic educational values to foster more holistic student development.